Coordinating culture change across the research landscape - McIntosh, Leslie D.; Hudson Vitale, Cynthia (Frontiers in Research Metrics and Analytics, 2023)
Scientific integrity necessitates applying scientific methods properly, collecting and analyzing data appropriately, protecting human subjects rightly, performing studies rigorously, and communicating findings transparently. But who is responsible for upholding research integrity, mitigating misinformation, and increasing trust in science beyond individual researchers? We posit that supporting the scientific reputation requires a coordinated approach across all stakeholders: funding agencies, publishers, scholarly societies, research institutions, and journalists and media, and policy-makers.